Crude oil emulsions: effect of water content and of self-assembly systems addition - de Castro Santana, Rejane; Castro Freitas Prado, Carolina; Ayupe de Souza Mendonça, Ricardo (Latin American Journal of Energy Research, 2021)
Water-in-oil emulsions of crude oil can present high viscosity, requiring techniques to viabilize their exploration and flow. As an alternative, oil-in-water microemulsions can be added on petroleum emulsions. Microemulsions are thermodynamically stable systems that modify the curvature of the water/oil interfacial fim, changing the stability and viscosity of these systems. Thus, the objectives of this work was to evaluate the effect of aqueous solution contente and of the self-assembly  systems incorporation on crude oil emulsions properties. Initially, crude oil was cheracterized by density measurements in diferent temperatures. Crude oil emulsions were produced with diferent conentrations (10-50% w/w) of brine solutions (27,870 ppm). According to the results of droplet size and kinetic stability, phase inversion from W/O to O/W ocurred at 30% (v/v) of brine solution. All emulsions showed lognormal droplet size distribution and Newtonian behavior, with viscosity ranging from 25.6 to 46.0 mPa.s. Subsequently, microemulsion formation was observed on 42% of pseudo-thernary driagram composed of water, xylene, and surfactant/co-surfactant (Triton/butanol). Microemulsion composed by 10% (w/w) water, 81%(w/w) Triton/butanol and 9% (w/w) xylene and surfactant solution conposed by 10% (w/w) water and 90% (w/w) Triton/butanol were added on W/O emulsion composed by crude oil and 20 % (w/w) of brine solution. No viscosity reduction was observed. However, droplet size decreased, showing the effect of self-assembly system use on crude oil emulsion microstructure.
Keywords: microemulsion; microstructure; rheology; stability; Triton-X-100